Analisis Kebijakan Pemerintah Indonesia Mengatasi Illegal Fishing di Kawasan Laut Arafura (2023-2024): Studi Kasus Kapal Run Zeng - Pesulima, Eunike; Roberto Octovianus Cornelis Seba; Christian H. J. de Fretes (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This research analyzes the Indonesian government’s policy responses to combating Illegal, Unreported, and Unregulated (IUU) Fishing in the Arafura Sea during 2023-2024, focusing on the case of the Run Zeng 03 and Run Zeng 05 vessels. These foreign-flagged vessels, owned by a Chinese company but registered under the Russian flag, were involved in illegal fishing and human rights violations against Indonesian fishery crew members. Using a qualitative descriptive approach supported by literature studies and official government data, this research analyzes how Indonesia implemented its maritime sovereignty through legal enforcement, inter-agency coordination, and international maritime diplomacy. The findings reveal that Indonesia’s measures, such as vessel monitoring AIS/VMS technology, law enforcement through arrests and seizures, and diplomatic engagement with flag states reflect a progressive but still reactive approach. The study identifies key challenges, including limited foreign authorities. This research highlights the need for an integrated policy framework that combines hard power (law enforcement and patrols) with soft power (international cooperation, economic diplomacy, and labor protection). The study concludes that a comprehensive and collaborative approach is essential to strengthen maritime governance and ensure sustainable, equitable management of Indonesia’s marine resources.